Saint Kitts and Nevis. Significant achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2020)
The main activities carried out by the Institute in Saint Kitts and Nevis during 2019 are identified, with respect to the needs and interests of the country, strengthening relations between the public and private sectors, food security and safety, apiculture and pest control in the citrus. Likewise, it contributed to the development of agrotourism, the incorporation of technology in agricultural processes, and good agricultural practices. Finally, support was given to agricultural and rural development, as well as the development of the mango production chain.